Effects of electrostimulation therapy on recovery from acute team-sport activity - Finberg, M.; Braham, R. A.; Goodman, C.; Gregory, P.; Peeling, P. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To assess the efficacy of a 1-off electrostimulation treatment as a recovery modality from acute teamsport exercise, directly comparing the benefits to contrast water therapy. Methods: Ten moderately trained male athletes completed a simulated team-game circuit (STGC). At the conclusion of exercise, participants then completed a 30-min recovery modality of either electrostimulation therapy (EST), contrast water therapy (CWT), or a passive resting control condition (CON). Twenty-four hours later, participants were required to complete a modified STGC as a measure of next-day performance. Venous blood samples were collected preexercise and 3 and 24 h postexercise. Blood samples were analyzed for circulating levels of interleukin-6 (IL-6) and C-reactive protein (CRP). Results: The EST trial resulted in significantly faster sprint times during the 24-h postrecovery than with CON (P < .05), with no significant differences recorded between EST and CWT or between CWT and CON (P > .05). There were no differences in IL-6 or CRP across all trials. Finally, the perception of recovery was significantly greater in the EST trial than in the CWT and CON (P < .05). Conclusions: These results suggest that a 1-off treatment with EST may be beneficial to perceptual recovery, which may enhance next-day performance.